Psychosocial, Educational, and Economic Impacts of COVID-19 - Hernández-Sánchez, Brizeida; Carlos Sánchez-García, José; Carrizo Moreira, António; Monteiro, Alcides A. (IntechOpen, 2023)
The COVID-19 pandemic had numerous negative effects on many aspects of life. This book provides a comprehensive overview of the psychosocial, educational, and economic impacts of the pandemic worldwide. It includes thirty-two chapters that highlight the importance of analyzing, evaluating, and carrying out appropriate treatments to prevent the mental and social consequences of the pandemic. Topics addressed include the psychological impacts of COVID-19 on different groups of people, including students, healthcare professionals, disadvantaged groups, and others; the educational impacts of COVID-19 on students, educators, students with disabilities, doctors, and so on; and the economic impacts of COVID-19 on managers, employees, residential care homes, and other businesses worldwide.